Market Chain Values of Capture Fisheries in the Lower Mekong River Basin and Implications for Management - Quan T. Lai; Ian G. Cowx; David Coates; Tran Chau Bao Tram; Hoang Duc Huy (Fisheries Management and Ecology, 2026)
Fish are an important commodity to communities in the Lower Mekong Basin (LMB), representing the most important protein source for millions of people in the region. Sustainable fisheries do not only require sustainable fish catches but also improve benefits and return to fishing communities through the fisheries value chain. Fish trade was surveyed in 12 provinces in the LMB to quantify the diversity, abundance and prices of fish species between landing sites and urban markets to understand mark‐up values through the value chain as an entry point to designing a strategic intervention to improve financial returns to fishers. Across the LMB, mark‐up in prices paid to fishers at landing sites and those reportedly charged to consumers in urban markets ranged from 36% to 110% on average, and reached as high as 611% for certain species. Cambodia and Vietnam exhibited similar average mark‐up values at 104% and 112% respectively (range 0% to 611%), while Lao PDR and Thailand both showed lower mark‐up prices at 36% (range 0%–175%). This highlights the potential for higher economic returns to fishing communities. Of 136 species in 11 major ecological guilds recorded from urban markets, potamodromous migratory main channel refuge seeker species (Guild 4) and potamodromous short‐distance migratory main channel spawner species (Guild 3) were the most diverse guilds that contributed 47% of species and were present in markets in all countries. Guild 3 also dominated the weight sold and individual species value, reflecting their high market demand in all countries. These findings show the added value generated in small‐scale inland fisheries systems in the LMB and justify further investment and research on how to improve financial returns to fishers, without necessarily increasing fish prices, which is essential to increase motivation for conservation of fish stocks and their habitats.

A Comparison of Diving Behavior of Goose‐Beaked and Dense‐Beaked Whales From Tagging Studies in Multiple Ocean Basins - Jay Barlow; Robin W. Baird; Janelle Badger; Gregory S. Schorr; Erin A. Falcone; Shannon N. Coates; Peter L. Tyack; Andrew J. Read; Leigh S. Hickmott; John W. Durban; Diane Claridge; Natacha Aguilar de Soto; et al. (Marine Mammal Science, 2026)
Studies of cetacean diving behavior in multiple locations in different ocean basins allow for an assessment of variability within and among populations. We examine foraging dive behaviors of goose‐beaked whales ( Ziphius cavirostris ) and dense‐beaked whales ( Mesoplodon densirostris ) using data from 132 tagged whales in seven locations in the Pacific and Atlantic Oceans and the Mediterranean Sea. Acoustic recording tags are used to identify foraging dives by the presence of echolocation. For other tag types, foraging dives are identified based on maximum dive depth. Five parameters are used to characterize foraging dives: maximum dive depth, foraging dive duration, dive cycle duration, and the mean and standard deviation of echolocation depths. We find that differences among dives within one tagged individual are typically larger than the differences among individuals or among locations, and that differences among individuals are typically similar in magnitude to differences among locations. Regression is used to estimate the mean and standard deviation of echolocation depths from maximum dive depth for dives without acoustic data. Composite values of foraging dive parameters (and standard deviations) are estimated as the average of all study locations.

Conservation translocation immediately reverses decline in imperiled sage-grouse populations - Mary B. Meyerpeter; Peter S. Coates; Megan C. Milligan; Brian G. Prochazka; Kade D. Lazenby; Steve Abele; John Tull; Katherine Miller; Jesse Kolar; Steven R. Mathews; David K. Dahlgren; David J. Delehanty (Biological Conservation, 2025)

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Insights into foraging behavior from multi-day sound recording tags on goose-beaked whales (Ziphius cavirostris) in the Southern California Bight - Shannon N. Coates; David A. Sweeney; Erin A. Falcone; Stephanie L. Watwood; Brenda K. Rone; Stacy L. DeRuiter; Jay Barlow; Karin A. Dolan; Ronald P. Morrissey; Nancy A. DiMarzio; Susan M. Jarvis; Russel D. Andrews; et al. (Frontiers in Marine Science, 2024)
Goose-beaked whales ( Ziphius cavirostris ) are deep-diving cetaceans known for their elusive nature and specialized foraging behavior. In 2019 and 2020, six telemetry tags were deployed on these whales in Southern California, resulting in 395 h of acoustic and diving data. Foraging dives were manually identified by the presence of echolocation pulses and buzzes, and generalized additive models assessed factors influencing foraging behavior. The median bathymetric depth at foraging sites was 1,419 m (IQR = 359), and the maximum dive depth was highly correlated with bathymetry depth. Individuals started echolocating on descent at a median depth of 410 m (IQR = 74); pulses were not observed shallower than 292 m. Echolocation ceased during the bottom phase for 81.6% of dives, at a median depth of 1,265 m (IQR = 472); pulses were not observed shallower than 587 m on ascent. The median depth of buzzes was 1,215 m (IQR = 479) with 63% occurring during the bottom phase. Deeper dives correlated with longer durations of diving and echolocation, greater echolocation end depths, and wider bottom phase echolocation depth inter-quartile range. The median difference between dive depth and bottom phase median echolocation depth was 98.3 m (IQR = 48.5), suggesting whales in this region forage in a narrow band close to the seafloor. In the San Nicolas Basin, individuals exhibited longer echolocation durations, produced more pulses, and started and ended echolocating at greater depths compared to adjacent regions. These records validate and expand upon previous studies, providing insights into factors influencing foraging behavior in an area with high anthropogenic disturbance.

Changes in plasma concentrations of per- and Polyfluoroalkyl substances after bariatric surgery in adolescents from the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) study - Brittney O. Baumert; Sandrah P. Eckel; Jesse A. Goodrich; Zhenjiang Li; Nikos Stratakis; Douglas I. Walker; Yinqi Zhao; Fabian Christoph Fischer; Scott Bartell; Damaskini Valvi; Xiangping Lin; Zoe Coates Fuentes; et al. (Science of The Total Environment, 2024)

Apomixis goes a long way: Genetic evidence of persistence and long‐distance seed dispersal in an ancient landscape - Nicola Delnevo; Rachel M. Binks; Stephen van Leeuwen; David J. Coates; Shelley McArthur; Bronwyn M. Macdonald; Margaret Hankinson; Margaret Byrne (Journal of Biogeography, 2024)
Aim Apomixis is a widespread trait in extreme environments worldwide, yet phylogeographical studies for species exhibiting these complex reproductive systems are still limited to temperate zones in the Northern Hemisphere. Through analyses of a combination of adult plants and seedlings, and nuclear and chloroplast DNA, we assessed the contemporary genetic outcomes of apomixis and phylogeographical patterns in an arid unglaciated landscape to understand the evolutionary trajectory of apomictic species. Location Pilbara bioregion, north‐western Australia. Taxon Senna glutinosa subsp. glutinosa . Materials and Methods Spatial patterns of genetic diversity and differentiation in three chloroplast regions and 17 nuclear microsatellite markers were evaluated in 480 plants from 20 populations of S. glutinosa subsp. glutinosa across the Pilbara bioregion. We also germinated and genotyped seed for a progeny analysis to quantify polyembryony and the relative frequency of asexual versus sexual reproduction. Results We found frequent polyembryony and a high proportion of asexual offspring (84.56%), resulting in low within‐population genotypic diversity. The nuclear dataset identified 72 multilocus lineages (MLLs) with moderate pairwise population genetic fixation and low differentiation among populations with no geographically structured genetic clustering. Chloroplast DNA showed high haplotype diversity and a widespread distribution of haplotypes. Only one peripheral population presented a single unique haplotype and MLL. Main Conclusions Analysis of this woody perennial in an arid landscape shows the influence of apomixis on genetic patterns and species persistence. Haplotype diversity was indicative of long‐term persistence within the ancient Pilbara region. Widespread distribution of haplotypes and sharing of several nuclear MLLs among distant populations indicated extensive seed dispersal throughout the study area. The combination of polyploidy, facultative apomixis and extensive seed dispersal maintains genetic variability within local populations and promotes the spread of advantageous genotypes across wide geographical distances. Therefore, apomixis, rather than an evolutionary ‘dead‐end’, can be regarded as a mechanism facilitating evolutionary success of apomictic species in extreme and complex environments.

Thirty-five-year timber harvesting disturbance effects on composition and biomass of tupelo-cypress (Nyssa-Taxodium) forested wetlands, southwest Alabama, USA - Cora Every; W. Michael Aust; David R. Carter; T. Adam Coates; Erik B. Schilling (Wetlands, 2023)

Using state-and-transition simulation models to scope post-fire success in restoring greater sage-grouse habitat - Elizabeth K. Orning; Julie A. Heinrichs; David A. Pyke; Peter S. Coates; Cameron L. Aldridge (Ecological Modelling, 2023)

Herbivore exclusion and water availability improve success across 76 translocations of 50 threatened plant species in a biodiversity hotspot with a Mediterranean climate - Leonie Monks; Jian Yen; Rebecca Dillon; Rachel Standish; David Coates; Margaret Byrne; Peter Vesk (Plant Ecology, 2023)

Low dose γ-radiation induced effects on wax moth (Galleria mellonella) larvae - David Copplestone; Christopher J. Coates; Jenson Lim (Science of The Total Environment, 2023)

Geothermal energy production adversely affects a sensitive indicator species within sagebrush ecosystems in western North America - Peter S. Coates; Brian G. Prochazka; Shawn T. O'Neil; Sarah C. Webster; Shawn Espinosa; Mark A. Ricca; Steven R. Mathews; Michael Casazza; David J. Delehanty (Biological Conservation, 2023)

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Targeting Sagebrush (Artemisia Spp.) Restoration Following Wildfire with Greater Sage-Grouse (Centrocercus Urophasianus) Nest Selection and Survival Models - Cali L. Roth; Shawn T. O’Neil; Peter S. Coates; Mark A. Ricca; David A. Pyke; Cameron L. Aldridge; Julie A. Heinrichs; Shawn P. Espinosa; David J. Delehanty (Environmental Management, 2022)
Unprecedented conservation efforts for sagebrush ( Artemisia spp.) ecosystems across the western United States have been catalyzed by risks from escalated wildfire activity that reduces habitat for sagebrush-obligate species such as Greater Sage-Grouse ( Centrocercus urophasianus ). However, post-fire restoration is challenged by spatial variation in ecosystem processes influencing resilience to disturbance and resistance to non-native invasive species, and spatial and temporal lags between slower sagebrush recovery processes and faster demographic responses of sage-grouse to loss of important habitat. Decision-support frameworks that account for these factors can help users strategically apply restoration efforts by predicting short and long-term ecological benefits of actions. Here, we developed a framework that strategically targets burned areas for restoration actions (e.g., seeding or planting sagebrush) that have the greatest potential to positively benefit sage-grouse populations through time. Specifically, we estimated sagebrush recovery following wildfire and risk of non-native annual grass invasion under four scenarios: passive recovery, grazing exclusion, active restoration with seeding, and active restoration with seedling transplants. We then applied spatial predictions of integrated nest site selection and survival models before wildfire, immediately following wildfire, and at 30 and 50 years post-wildfire based on each restoration scenario and measured changes in habitat. Application of this framework coupled with strategic planting designs aimed at developing patches of nesting habitat may help increase operational resilience for fire-impacted sagebrush ecosystems.

Rodent suppression of seedling establishment in tropical pasture - Crystal A. Guzmán; Henry F. Howe; David H. Wise; Rosamond I. Coates; Jenny Zambrano (Oecologia, 2021)

Wildfire and the ecological niche: Diminishing habitat suitability for an indicator species within semi‐arid ecosystems - Shawn T. O’Neil; Peter S. Coates; Brianne E. Brussee; Mark A. Ricca; Shawn P. Espinosa; Scott C. Gardner; David J. Delehanty (Global Change Biology, 2020)
Globally accelerating frequency and extent of wildfire threatens the persistence of specialist wildlife species through direct loss of habitat and indirect facilitation of exotic invasive species. Habitat specialists may be especially prone to rapidly changing environmental conditions because their ability to adapt lags behind the rate of habitat alteration. As a result, these populations may become increasingly susceptible to ecological traps by returning to suboptimal breeding habitats that were dramatically altered by disturbance. We demonstrate a multistage modeling approach that integrates habitat selection and survival during the key nesting life‐stage of a bird species of high conservation concern, the greater sage‐grouse ( Centrocercus urophasianus ; hereafter, sage‐grouse). We applied these spatially explicit models to a spatiotemporally robust dataset of sage‐grouse nest locations and fates across wildfire‐altered sagebrush ecosystems of the Great Basin ecoregion, western United States. Female sage‐grouse exhibited intricate habitat selection patterns that varied across regional gradients of ecological productivity among sagebrush communities, but often selected nest sites that disproportionately resulted in nest failure. For example, 23% of nests occurred in wildfire‐affected habitats characterized by reduced sagebrush cover and greater composition of invasive annual grasses. We found survival of nests was negatively associated with wildfire‐affected areas, but positively associated with higher elevations with increased ruggedness and overall shrub cover. Strong site fidelity likely drove sage‐grouse to continue nesting in habitats degraded by wildfire. Hence, increasing frequency and extent of wildfire may contribute disproportionately to reduced reproductive success by creating ecological traps that act as population sinks. Identifying such habitat mismatches between selection and survival facilitates deeper understanding of the mechanisms driving reduced geographic niche space and population decline at broad spatiotemporal scales, while guiding management actions to areas that would be most beneficial to the species.

Lumbar spinal cord microglia exhibited increased activation in aging dogs compared with young adult dogs - Christine M. Toedebusch; Virginia B. Garcia; John C. Snyder; Maria R. Jones; David J Schulz; Gayle C. Johnson; Eric Villalón; Joan R. Coates; Michael L. Garcia (GeroScience, 2020)

Refining expectations for environmental characteristics of refugia: two ranges of differing elevation and topographical complexity are mesic refugia in an arid landscape - Margaret Byrne; Melissa A. Millar; David J. Coates; Bronwyn M. Macdonald; Shelley M. McArthur; Michael Zhou; Stephen van Leeuwen (Journal of Biogeography, 2017)
Aim Topographically complex areas are hypothesized to be mesic refugia in arid environments during periods of climatic change. We tested the hypothesis that an elevated and topographically complex range has been a historical refugium in an arid environment during Pleistocene climatic oscillations for a widespread eucalypt. Location Pilbara region, north‐west Australia. Methods We evaluated genetic diversity and differentiation in chloroplast and nuclear genomes using microsatellite loci in 20 populations of Eucalyptus leucophloia from across the distribution in the Pilbara bioregion, including two ranges with differing topographical complexity and elevation. We evaluated phylogeographical structure using Permut and Network analysis, and assessed genetic structure using principle coordinate (PCoA) and Bayesian analyses. Results We found moderate levels of genetic diversity and low genetic differentiation among populations, typical of widespread eucalypts. There was no evidence of genetic structure across the sampled range. Populations in both the Hamersley and Chichester ranges showed higher levels of chloroplast haplotype and nuclear diversity than those in surrounding areas. Diversity was negatively correlated with evapotranspiration, and positively correlated with precipitation. Main conclusions Genetic signals of high diversity and low differentiation indicated population persistence throughout historical climate change in ranges, with a signal of expansion in surrounding areas. Our analysis was consistent with the hypothesis of the elevated, topographically complex Hamersley Range acting as a refugium, but revealed an unexpected result of the lower elevation, less rugged Chichester Range also being a refugium. Our results suggest refinement to expectations of environmental characteristics that facilitate persistence, where thresholds of mesic environments for refugia may be lower than expected and moisture availability may be an important contributory aspect of elevation and topographical complexity. In contrast to patterns in reptile species, lack of genetic structure associated with geological substrate and geomorphological features indicates dispersal is not impeded by these landscape features for this widespread eucalypt.

Does population distribution matter? Influence of a patchy versus continuous distribution on genetic patterns in a wind‐pollinated shrub - Tanya M. Llorens; Sarah‐Louise Tapper; David J. Coates; Shelley McArthur; Margaret Hankinson; Margaret Byrne (Journal of Biogeography, 2017)
Aim Uniform spatial population distributions are predicted to result in lower among‐population genetic differentiation and higher within‐population genetic diversity than naturally patchy distributions, but there have been surprisingly few attempts to isolate this effect from confounding factors. We studied the widespread wind‐pollinated shrub Allocasuarina humilis that is common in a geologically stable landscape characterized by long‐term population persistence to test the influence of semi‐continuous versus patchy population distributions on genetic patterns. We also investigated whether A. humilis shows the high population connectedness and genetic diversity typically associated with wind pollination, a relatively uncommon and little‐studied syndrome in this landscape. Location Heath‐shrublands (‘heath’) and forests of south‐western Australia. Methods Populations were sampled from heath and forest regions, which respectively exhibited semi‐continuous and patchy population distributions. Genetic structure and diversity were assessed for 27 populations using eight nuclear microsatellite markers and three chloroplast regions. Phylogeographical history was examined using Bayesian phylogeny reconstruction, parsimony analysis and tests of expansion. Results High haplotype diversity is consistent with long‐term population persistence across most of the species’ range. Nuclear markers showed low overall population differentiation and no geographical structure over c . 900 km, reflecting extensive pollen dispersal. For both marker types, patchily distributed forest populations were substantially more differentiated with significantly lower within‐population diversity than semi‐continuous heath populations. Phylogeographical analysis revealed evidence for earlier colonization of heath than forest and recent expansion into wetter forests, consistent with progressive long‐term climatic drying. Main conclusions High population connectedness and genetic diversity probably resulted from wind pollination in combination with dioecy and long life span. Patchy population distributions appear to have influenced genetic structure and diversity through lower pollen and seed dispersal, lower effective population sizes and greater genetic drift. Our approach illustrates the value of minimizing confounding variables by testing the effect of a variable ecological trait within a single species.

The role of fire and a long‐lived soil seed bank in maintaining persistence, genetic diversity and connectivity in a fire‐prone landscape - Donna Bradbury; Sarah‐Louise Tapper; David Coates; Shelley McArthur; Margaret Hankinson; Margaret Byrne (Journal of Biogeography, 2016)
Aim Terrestrial plant ecology and evolution is significantly influenced by the phenomenon of fire, but studies of its potential impact on intraspecific genetic variation and phylogeography are rare. This understanding will be important for predicting the biogeographical consequences of changing fire regimes under global climate change. Here, we asked whether changing historical fire regimes, together with climatic and geological history, have influenced phylogeographical patterns in a fire‐ephemeral vine. We also asked whether demographic stochasticity associated with a fire‐ephemeral life history results in nuclear genetic drift as expected from spatio‐temporal patchiness, or if this effect is buffered by the connectivity and diversity afforded by a persistent soil seed bank. Location The fire‐prone, mediterranean‐type climate region of south‐western Australia. Methods We used Bayesian phylogeny reconstruction and statistical tests of demographic expansion based on variation at three non‐coding chloroplast sequence regions ( atpF, ndhF–rpl32, psbD–trnT ) to reconstruct phylogeographical history. Nuclear diversity and population structure at 11 microsatellite loci were investigated for evidence of genetic drift. Results Evidence for prolonged persistence and a lack of vicariance within the species range was found, together with strong evidence of historical demographic expansion. Contrary to expectations, there was little evidence of nuclear genetic drift despite strong, above‐ground spatio‐temporal population patchiness. Main conclusions Our findings suggest that a late Pleistocene increase in fire frequency may have led to demographic expansion in this fire‐ephemeral species; alternatively, the expansion signal may be an inherent feature of fire ephemerals with a persistent soil seed bank. Prolonged climatic stability has likely fostered persistence within the species range in contrast to contraction and vicariance. The notable lack of genetic drift implies a role for ample pollen dispersal and a long‐lived soil seed bank in the maintenance of diversity and connectivity in an otherwise stochastic, fire‐driven system.

How does the post‐fire facultative seeding strategy impact genetic variation and phylogeographical history? The case of Bossiaea ornata (Fabaceae) in a fire‐prone, mediterranean‐climate ecosystem - Donna Bradbury; Sarah‐Louise Tapper; David Coates; Margaret Hankinson; Shelley McArthur; Margaret Byrne (Journal of Biogeography, 2016)
Aim Fire regimes are a significant driver of plant adaptation and evolution, and projected changes under a changing climate will have significant implications for demographic and evolutionary responses of plant populations in fire‐prone regions globally. We tested predictions regarding level and pattern of genetic variation within a model post‐fire facultative seeder, Bossiaea ornata (Fabaceae), that exhibits a combination of both post‐fire resprouting and seeding strategies. Location Fire‐prone forests in the mediterranean‐climate region of south‐western Australia. Methods We genotyped individuals with eight microsatellite markers and four non‐coding chloroplast sequence regions to assess population genetic variation and reconstruct phylogeographical history. Results Extremely high levels of chloroplast ( H D = 0.95) and nuclear ( H E = 0.81) diversity were detected. Nuclear population differentiation was weak ( F ST = 0.06) and chloroplast phylogeographical structure was absent. A significant excess of rare chloroplast haplotypes was detected ( D , F S , R 2 ; all P 0.01), consistent with demographic expansion. Main conclusions Results suggest that a facultative seeding life‐history affords the benefits of both obligate resprouting and obligate seeding strategies in terms of resistance and resilience to fire. High diversity and low differentiation are likely driven by long generational overlap (resprouter feature), regular post‐fire population supplementation from a persistent soil seed bank (seeder feature) and long‐term stability. Expansion signals may be a feature of species with regular, synchronous post‐fire recruitment from a soil seed bank, rather than evidence of a single range or demographic expansion event, as typically interpreted. The facultative seeding strategy may therefore offer resilience to potential increases in fire frequency under a changing climate in fire‐prone regions.

Isolation and characterisation of ten microsatellite loci from a Western Australian tree, Banksia sessilis (Proteaceae) - Heidi Nistelberger; Shelley McArthur; David Coates; Margaret Byrne (Conservation Genetics Resources, 2015)

Strategic taxonomy in a biodiverse landscape: a novel approach to maximizing conservation outcomes for rare and poorly known flora - Juliet A. Wege; Kevin R. Thiele; Kelly A. Shepherd; Ryonen Butcher; Terry D. Macfarlane; David J. Coates (Biodiversity and Conservation, 2015)

Isolation and characterization of 11 microsatellite primer pairs for the southwest Australian forest understorey species Kennedia coccinea (Fabaceae: Phaseoleae) - Donna Bradbury; Shelley McArthur; David Coates; Margaret Byrne (Conservation Genetics Resources, 2014)

Characterisation of microsatellite DNA markers for Mirbelia bursarioides A.M.Monro & Crisp ms. - Melissa A. Millar; Margaret Byrne; David J. Coates; J. Dale Roberts (Conservation Genetics Resources, 2014)

Characterisation of microsatellite DNA markers for Grevillea globosa C. A. Gardner - Melissa A. Millar; Margaret Byrne; David J. Coates; J. Dale Roberts (Conservation Genetics Resources, 2014)

Isolation via 454 sequencing, and characterisation of microsatellite markers for the Pilbara endemic Acacia atkinsiana (Fabaceae) - Esther Levy; Margaret Byrne; David J. Coates; Stephen J. van Leeuwen; Shelley McArthur; Bronwyn Macdonald; Michael G. Gardner (Conservation Genetics Resources, 2014)

Characterisation of microsatellite DNA markers for the Wiry Honey Myrtle, Melaleuca nematophylla Craven - Melissa A. Millar; Margaret Byrne; David J. Coates; J. Dale Roberts (Conservation Genetics Resources, 2014)

Isolation and characterization of 11 microsatellite loci in the short-range endemic shrub Grevillea georgeana McGill (Proteaceae) - Heidi Nistelberger; David Coates; Margaret Byrne; J. Dale Roberts (Conservation Genetics Resources, 2014)

Characterisation of microsatellite DNA markers for Grevillea paradoxa (F. Muell) - Melissa A. Millar; Margaret Byrne; David J. Coates; J. Dale Roberts (Conservation Genetics Resources, 2014)

Isolation and characterisation of 14 microsatellite loci from a short-range endemic, Western Australian tree, Banksia arborea (C.A. Gardner) - Heidi Nistelberger; J. Dale Roberts; David Coates; Margaret Byrne (Conservation Genetics Resources, 2013)

Isolation and characterisation of 11 microsatellite loci from the Western Australian Spirostreptid millipede, Atelomastix bamfordi - Heidi Nistelberger; Margaret Byrne; J. Dale Roberts; David Coates (Conservation Genetics Resources, 2013)

A preliminary assessment of changes in plant-dwelling insects when threatened plants are translocated - Melinda L. Moir; Peter A. Vesk; Karl E. C. Brennan; Lesley Hughes; David A. Keith; Michael A. McCarthy; David J. Coates; Sarah Barrett (Journal of Insect Conservation, 2012)

Considering Extinction of Dependent Species during Translocation, Ex Situ Conservation, and Assisted Migration of Threatened Hosts - MELINDA L. MOIR; PETER A. VESK; KARL E. C. BRENNAN; ROBERT POULIN; LESLEY HUGHES; DAVID A. KEITH; MICHAEL A. McCARTHY; DAVID J. COATES (Conservation Biology, 2012)
Translocation, introduction, reintroduction, and assisted migrations are species conservation strategies that are attracting increasing attention, especially in the face of climate change. However, preventing the extinction of the suite of dependent species whose host species are threatened is seldom considered, and the effects on dependent species of moving threatened hosts are unclear. There is no published guidance on how to decide whether to move species, given this uncertainty. We examined the dependent–host system of 4 disparate taxonomic groups: insects on the feather‐leaf banksia ( Banksia brownii ) , montane banksia ( B. montana ), and Stirling Range beard heath ( Leucopogon gnaphalioides ); parasites of wild cats; mites and ticks on Duvaucel's gecko ( Hoplodactylus duvaucelii ) and tuatara ( Sphenodon punctatus ); and internal coccidian parasites of Cirl Bunting ( Emberiza cirlus ) and Hihi ( Notiomystis cincta ). We used these case studies to demonstrate a simple process for use in species‐ and community‐level assessments of efforts to conserve dependents with their hosts. The insects dependent on Stirling Range beard heath and parasites on tigers ( Panthera tigris ) appeared to represent assemblages that would not be conserved by ex situ host conservation. In contrast, for the cases of dependent species we examined involving a single dependent species (internal parasites of birds and the mite Geckobia naultina on Duvaucel's gecko), ex situ conservation of the host species would also conserve the dependent species. However, moving dependent species with their hosts may be insufficient to maintain viable populations of the dependent species, and additional conservation strategies such as supplementing populations may be needed .

The Role of Botanic Gardens in the Science and Practice of Ecological Restoration - KATE A. HARDWICK; PEGGY FIEDLER; LYNDON C. LEE; BRUCE PAVLIK; RICHARD J. HOBBS; JAMES ARONSON; MARTIN BIDARTONDO; ERIC BLACK; DAVID COATES; MATTHEW I. DAWS; KINGSLEY DIXON; STEPHEN ELLIOTT; et al. (Conservation Biology, 2011)
Many of the skills and resources associated with botanic gardens and arboreta, including plant taxonomy, horticulture, and seed bank management, are fundamental to ecological restoration efforts, yet few of the world's botanic gardens are involved in the science or practice of restoration. Thus, we examined the potential role of botanic gardens in these emerging fields. We believe a reorientation of certain existing institutional strengths, such as plant‐based research and knowledge transfer, would enable many more botanic gardens worldwide to provide effective science‐based support to restoration efforts. We recommend botanic gardens widen research to include ecosystems as well as species, increase involvement in practical restoration projects and training practitioners, and serve as information hubs for data archiving and exchange.

Characterisation of microsatellite markers for the rare and critically endangered Banksia brownii (Proteaceae) - Shelley L. McArthur; David J. Coates (Conservation Genetics Resources, 2010)

Maintenance of high pollen dispersal in Eucalyptus wandoo, a dominant tree of the fragmented agricultural region in Western Australia - Margaret Byrne; Carole P. Elliott; Colin J. Yates; David J. Coates (Conservation Genetics, 2008)

Influence of Mouthpiece Geometry on the Aerosol Delivery Performance of a Dry Powder Inhaler - Matthew S. Coates; Hak-Kim Chan; David F. Fletcher; Herbert Chiou (Pharmaceutical Research, 2007)

Active integration: new strategies for transgenesis - Eric T. Shinohara; Joseph M. Kaminski; David J. Segal; Pawel Pelczar; Ravindra Kolhe; Thomas Ryan; Craig J. Coates; Malcolm J. Fraser; Alfred M. Handler; Ryuzo Yanagimachi; Stefan Moisyadi (Transgenic Research, 2007)

Composition of the pollinator community, pollination and the mating system for a shrub in fragments of species rich kwongan in south-west Western Australia - Colin J. Yates; David J. Coates; Carole Elliott; Margaret Byrne (Biodiversity and Conservation, 2007)

Genetic variation and the mating system in the rare Acacia sciophanes compared with its common sister species Acacia anfractuosa (Mimosaceae) - David J. Coates; Genevieve Tischler; Jen A. McComb (Conservation Genetics, 2006)

Influence of Air Flow on the Performance of a Dry Powder Inhaler Using Computational and Experimental Analyses - Matthew S. Coates; Hak-Kim Chan; David F. Fletcher; Judy A. Raper (Pharmaceutical Research, 2005)

The Role of Capsule on the Performance of a Dry Powder Inhaler Using Computational and Experimental Analyses - Matthew S. Coates; David F. Fletcher; Hak-Kim Chan; Judy A. Raper (Pharmaceutical Research, 2005)

Genetic divergence among and diversity within two rare Banksia species and their common close relative in the subgenusIsostylis R.Br. (Proteaceae) - Linda M. Broadhurst; David J. Coates (Conservation Genetics, 2004)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

TheHermes element fromMusca domestica can transpose in four families of cyclorrhaphan flies - Abhimanyu Sarkar; Craig J. Coates; Steven Whyard; Ute Willhoeft; Peter W. Atkinson; David A. O'Brochta (Genetica, 1997)

The Hermes element from Musca domestica can transpose in four families of cyclorrhaphan flies - Abhimanyu Sarkar; Craig J. Coates; Steven Whyard; Ute Willhoeft; Peter W. Atkinson; David A. O'Brochta (Genetica, 1997)